2015
DOI: 10.1002/jsfa.7208
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage protection against free radicals of two antioxidant neolignan glucosides from sugarcane molasses

Abstract: The isolated neolignan glucosides from sugarcane molasses are able to protect DNA from oxidative damage caused by free radicals. This is the first identification of these two compounds in sugarcane molasses. The sugarcane molasses can therefore be used as potential nutraceutical preventative agents, and the findings may foster the utilization of this by-product as a bioresource-based product. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The ability of compounds to protect pUC19 plasmid DNA against strand breakage was investigated as described previously, [15,38,39] with some modifications. Plasmid DNA was oxidised by UV treatment in the presence of polyphenol monomers or Morus alba L. twig extract and monitored by 1% agarose gel electrophoresis.…”
Section: Evaluation Of Dna Damage Protection Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of compounds to protect pUC19 plasmid DNA against strand breakage was investigated as described previously, [15,38,39] with some modifications. Plasmid DNA was oxidised by UV treatment in the presence of polyphenol monomers or Morus alba L. twig extract and monitored by 1% agarose gel electrophoresis.…”
Section: Evaluation Of Dna Damage Protection Activitymentioning
confidence: 99%
“…Gels were stained with ethidium bromide and photographed using a gel documentation system (Bio-Rad Laboratories, Inc. USA). [41,42] Analysis of polyphenol monomers by HPLC Extracts were analysed using HPLC, and polyphenol monomers were detected as described previously [38] using a reversed-phase Inert Sustain C18 column (250 mm x 4.6 mm, 5 μm particle size, SHIMADZU, Tokyo, Japan) with a sample volume of 10 μL and a column temperature of 30°C.…”
Section: Evaluation Of Dna Damage Protection Activitymentioning
confidence: 99%
“…The water fraction was further partitioned with EtOAc and n -BuOH. All fractions were subjected to a combination of column chromatography, preparative HPLC, and preparative TLC using silica gel and octadecylsilyl (ODS) to give seven new butanolides, peltanolides A–G ( 1 – 7 ), and two new lignan glycosides, peltasides A ( 8 ) and B ( 9 ), as well as eleven known compounds, tambouranolide ( 10 ) [15], deoxypodophyllotoxin ( 11 ) [16], podorhizol ( 12 ) [17], bursehernin ( 13 ) [18], (2 S ,3 S )-(+)-5′-methoxyyatein ( 14 ) [19], epiashantin ( 15 ) [20], epieudesmin ( 16 ) [21], (1 S ,3a R ,4 R ,6a R )-1-(3,4-dimethoxyphenyl)-4-(3′,4′,5′-trimethoxyphenyl)tetrahydro-1 H ,3 H -furo-[3– c ]furan ( 17 ) [20], (7 R ,8 S )-dehydrodiconiferyl alcohol-4- O -β- d -glucoside ( 18 ) [22], alaschanioside A ( 19 ) [23], and osmanthuside H ( 20 ) [24]. The structures of all known compounds were identified by comparison of their spectroscopic data with reported values.…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen species (ROS), which are very transient species, can cause DNA damage . It has been demonstrated that ROS‐derived DNA damage can be reduced by antioxidants …”
Section: Introductionmentioning
confidence: 99%
“…1 It has been demonstrated that ROS-derived DNA damage can be reduced by antioxidants. [8][9][10][11][12][13] Rice protein has its own protein components, including albumin (water soluble), globulin (salt soluble), glutelin (alkali / acid soluble), and prolamin (alcohol soluble), in which glutelin and prolamin are major storage proteins. [15][16][17] Rice and rice protein have numerous physiological functions, [18][19][20][21][22][23] in which some studies have clearly indicated an association between rice protein consumption and a reduced risk of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%